Common fixed point theorems for commuting k-uniformly Lipschitzian mappings - M. Elamrani; A. B. Mbarki; B. Mehdaoui (International Journal of Mathematics and Mathematical Sciences)
We give a common fixed point existence theorem for any sequence of commuting k-uniformly Lipschitzian mappings (eventually, for k=1 for any sequence of commuting nonexpansive mappings) defined on a bounded and complete metric space (X,d) with uniform normal structure. After that we deduce, by using the Kulesza and Lim (1996), that this result can be generalized to any family of commuting k-uniformly Lipschitzian mappings.